UMA ABORDAGEM BASEADA EM ENGENHARIA DIRIGIDA POR MODELOS PARA SUPORTAR O TESTE DE SISTEMAS DE SOFTWARE NA PLATAFORMA DE COMPUTAÇÃO EM NUVEM - OLIVEIRA, Jéssica Bassani de (2012)
We present an approach to support the creation of test cases for software systems in cloud computing environments. This approach is based on Model Driven Engineering (MDE). A framework, a methodology and metamodels are proposed to support the generation of test cases. Metamodels for cloud computing environments and transformation definitions are proposed. Two illustrative examples help to understand our approach and the steps to apply it. A prototype implementing the proposed framework is presented and it works together with MT4MDE and SAMT4MDE to generate semi-automatically transformation definitions and contribute to the semiautomatic creation of testing model and test code for cloud computing platforms. We present an evaluation of our approach and compare it with other approaches, detaching main differences, including advantages and disavantages.